2021
DOI: 10.1002/bem.22372
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Low‐Frequency Pulsed Electromagnetic Field and Melatonin on Ovariectomy‐Induced Bone Loss in Mice

Abstract: Pulsed electromagnetic field (PEMF) therapy and melatonin (MEL) supplementation are expected to be important strategies for the treatment of osteoporosis. The aim of the current study was to investigate the efficacy of PEMF therapy, MEL supplementation, a combination of PEMF therapy, and MEL supplementation (PEMF + MEL) in mice with bilateral ovariectomy (OVX)-induced osteoporosis. Forty 12-week-old female C57/BL mice were randomly assigned to five groups (n = 8/group): OVX, PEMF, MEL, PEMF + MEL, and sham-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…Melatonin feeding could improve bone mass and relieve bone loss in OVX mice (Gürler et al, 2019). Histological detection of bone tissues indicated that melatonin increases the expression of Collagen I and BMP2 but decreases the expression of PRMT1 and TRAP (Choi et al, 2021;Huang et al, 2021). These data demonstrate that melatonin has positive effects on osteogenesis and negative effects on osteoclastogenesis in animal models, which is consistent with the results at the cellular level.…”
Section: In Vivo Experimentssupporting
confidence: 86%
“…Melatonin feeding could improve bone mass and relieve bone loss in OVX mice (Gürler et al, 2019). Histological detection of bone tissues indicated that melatonin increases the expression of Collagen I and BMP2 but decreases the expression of PRMT1 and TRAP (Choi et al, 2021;Huang et al, 2021). These data demonstrate that melatonin has positive effects on osteogenesis and negative effects on osteoclastogenesis in animal models, which is consistent with the results at the cellular level.…”
Section: In Vivo Experimentssupporting
confidence: 86%
“…In total, 10 females from the sham group underwent a sham ovariectomy (sham). During sham surgery, the animals underwent a similar procedure, except for the removal of the ovaries [55,56].…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Te PEMF stimulation parameter was based on our previous data: square wave/1.6 mT/75 Hz. [28][29][30]. We used a handheld Gaussian meter (HT201; Hengtong, China) to measure the magnetic feld intensity.…”
Section: Pemf Treatmentmentioning
confidence: 99%
“…We used a handheld Gaussian meter (HT201; Hengtong, China) to measure the magnetic feld intensity. Details of the PEMF exposure device can be found in our previous studies [28].…”
Section: Pemf Treatmentmentioning
confidence: 99%
See 1 more Smart Citation